Updated soil to fruit concentration ratios for radiocaesium compiled under the IAEA MODARIA II Programme. (1st June 2022) - Doering, C; Carini, F; Sato, M; Howard, BJ; Harbottle, AR; Brown, J; Twining, J; Velasco, H
Abstract: Under the International Atomic Energy Agency (IAEA) Modelling and Data for Radiological Impact Assessments (MODARIA II) Programme, Working Group 4 activities included collating radionuclide transfer data from Japan following the Fukushima Daiichi Nuclear Power Plant accident and separately collating concentration ratio (CR) data for root uptake of radionuclides by crops grown in tropical and arid climates. In this paper, the newly compiled radiocaesium CR data for fruit from Japan, tropical and arid climates have been combined with the data originally compiled for the IAEA Technical Reports Series No. 472 (TRS 472) and additional data identified from the literature to produce an enhanced MODARIA II dataset of fruit radiocaesium CR values. Statistical analysis of the MODARIA II dataset by climate class (based on the Köppen–Geiger climate classification) indicated that the CR values for tropical climates were significantly higher ( p < 0.05) than those for arid, temperate and cold climates. Statistical analysis of the MODARIA II dataset by soil group (based on soil texture) indicated that the CR values for coral sand soil (tropical climates only) and organic soil (temperate climates only) were significantly higher ( p < 0.05) than those for the clay, loam and sand soil groups. Statistical analysis of the MODARIA II dataset by plant group (based on plant morphology) indicated that the CR values for non-woody trees (tropical climate bias) were significantly higher ( p < 0.05) than those for herbaceous plants, shrubs and woody trees. Comparison of the MODARIA II dataset with original TRS 472 values showed only small changes in the fruit radiocaesium CR values for herbaceous plants and shrubs in temperate climates. There was a decrease in the CR values for woody trees in temperate climate across all soil groups. There was also a decrease in the CR values for tropical climates for all comparable soil groups.